2022
DOI: 10.12968/ajmw.2021.0024
|View full text |Cite
|
Sign up to set email alerts
|

Early discontinuation of Implanon and associated factors among women in public health facilities of the Hawassa administration, south Ethiopia

Abstract: Background/Aims Despite improving availability and use of the contraceptive Implanon, early discontinuation is a public health concern. A significant proportion of women discontinue using Implanon before it is due to be removed, which poses a health concern and may lead to contraceptive failure. Only 8% of married women in Ethiopia use contraceptive implants. There is a paucity of information on factors associated with early discontinuation of Implanon. This study's aims were to assess early discontinuation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This nding is consistent with the nding in the study conducted in public health facilities in Ethiopia where women were more likely to have early implant removal if they desired to conceive in the near future (< 2 years) as compared to one who desired to conceive later. (24) This might be due to women who, at the time of implant insertion, may have experienced a pregnancy loss, or were anticipating completing their career obligations soon but still desired to have children in the near future (24,25). While no studies directly link career obligations to early implant removal, women may choose implants either to limit family size after reaching their desired number of children or to space pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…This nding is consistent with the nding in the study conducted in public health facilities in Ethiopia where women were more likely to have early implant removal if they desired to conceive in the near future (< 2 years) as compared to one who desired to conceive later. (24) This might be due to women who, at the time of implant insertion, may have experienced a pregnancy loss, or were anticipating completing their career obligations soon but still desired to have children in the near future (24,25). While no studies directly link career obligations to early implant removal, women may choose implants either to limit family size after reaching their desired number of children or to space pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Addressing the factors that contribute to early Implanon discontinuation is essential to ensure safe and reliable services to women in the reproductive age group through appropriate use of contraceptive methods and method switching. In Ethiopia, studies assessing early implanon discontinuation and associated factors among implanon user have contributed a range of findings [7,8,[13][14][15][16][17]. These small and fragmented studies revealed that early discontinuation of implanon ranged from 16% in Ofla District, Tigray, Northern Ethiopia [18], to 65% in Debre-tabor town, Amhara regional state [13].…”
Section: Study Selectionmentioning
confidence: 99%
“…Such discrepancy has not been yet investigated. Regarding associated factors, previous studies have cited mothers' experienced side effect [7,[13][14][15][16][17][18], services dissatisfaction [13][14][15]18], lack of appointment after insertion [13][14][15][16]18], and in adequate pre-insertion counselling [7,8,[14][15][16][17] as the common factors contributing to early implanon discontinuation among women's of implanon users in Ethiopia.…”
Section: Study Selectionmentioning
confidence: 99%